Tolerance Education and Rejuvenation of Islamic Religious Education (IRE) Learning on Independent Curriculum - Edi Nurhidin (Institut Agama Islam An-Nawawi Purworejo, 2023)
The prevalence of intolerance has become increasingly pervasive in educational institutions. Recent research findings have demonstrated an increase in most intolerant comprehension and attitudes among secondary school students. This study distinguishes itself from other research by utilizing tolerance education to rejuvenate Islamic religious education learning, employing an independent learning curriculum approach. This study employs a qualitative research methodology, using a literature review as its primary strategy. The study's findings indicate that it is necessary to implement a complete integration approach that encompasses all levels of high school classes to revitalize tolerance education effectively. Another significant discovery pertains to the necessity of enhancing the appeal of tolerance education by establishing connections with real-life contexts, particularly the environment. Additionally, including parents and the community in this endeavor is crucial while employing an accurate evaluation approach to evaluate the development of tolerant attitudes.